From Rumi to the whirling dervishes - Feldman, Walter Zev, 1949- (Edinburgh)
xxiii, 280 sayfa
Keywords: “A pioneering study that illuminates the connection of music, poetry, mystical praxis and social history underlying the ceremony of the Mevlevi Dervishes. Mevlana Jalaluddin Rumi, whose life and mystical poetry provided the inspiration for the Mevlevi Sufi order, is one of the world's best-known poets, yet the centuries-long musical tradition cultivated by the Mevleviye remains much less known. In this deeply researched book, renowned scholar Walter Feldman traces the historical development of Mevlevi music and brings to light the remarkable musical and mystical aesthetics of the Mevlevi ayin - the instrumental and vocal accompaniment to the sublime ceremony of the 'Whirling' Dervishes.“ --